2020
DOI: 10.1039/d0ta02825h
|View full text |Cite
|
Sign up to set email alerts
|

MOF-derived Fe,Co@N–C bifunctional oxygen electrocatalysts for Zn–air batteries

Abstract: MOF-derived Fe,Co@N-C bifunctional electrocatalysts for oxygen reduction reactions and oxygen evolution reactions have been prepared via a scalable method, exhibiting ultra-high catalytic activity and promising performance in Zn–air batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(78 citation statements)
references
References 45 publications
0
78
0
Order By: Relevance
“…Two or more kinds of inorganic centers from metal ions or clusters can be incorporated in bimetallic-MOFs, coordinating with different organic ligands, or linkers containing different metals. To obtain a controlled composition, different metals can play an important role [ 141 , 142 ]. Moreover, the M 1 and M 2 coupling is vital for supporting the electrocatalytic performance.…”
Section: Energy Applications Of Mof-derived Electrocatalystsmentioning
confidence: 99%
“…Two or more kinds of inorganic centers from metal ions or clusters can be incorporated in bimetallic-MOFs, coordinating with different organic ligands, or linkers containing different metals. To obtain a controlled composition, different metals can play an important role [ 141 , 142 ]. Moreover, the M 1 and M 2 coupling is vital for supporting the electrocatalytic performance.…”
Section: Energy Applications Of Mof-derived Electrocatalystsmentioning
confidence: 99%
“…[185] Recently, Duan et al fabricated hierarchical Fe,Co@N-C bimetallic materials derived from Fe 3+ and glucosamine-encapsulated ZIF-8/67 as illustrated in Figure 12a. [186] Moreover, they evaluated the ORR and OER performance of FeCoN 8 using DFT computations and free energy diagrams as illustrated in Figure 12b. They concluded that the overpotential of FeCoN 8 was less than individual CoN 4 or FeN 4 .…”
Section: Transition Metal-doped Carbonsmentioning
confidence: 99%
“…Figure 12. a) Synthesis scheme of FeCo-N-C-T. b) Free energy diagram of CoN 4 , FeN 4,and FeCoN 8 at the equilibrium potential (U 0 = 0.402 V) for ORR and OER and ORR. Reproduced with permission [186]. Copyright 2020, The Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…For decades, numerous researches on highly efficient bifunctional oxygen electrocatalysts have been published. Table 1 summarizes recently studied catalysts with high bifunctional activities, which could be divided to noble metal‐based catalysts [ 68–74 ] , carbon‐based metal‐free catalysts, [ 75–80 ] and transition metal‐based catalysts (including metal/metal alloys [ 81–85 ] , oxides [ 86–88 ] , hydroxides [ 89–92 ] , chalcogenides [ 93–95 ] , phosphides [ 96–99 ] , nitrides [ 100–102 ] , carbides, [ 103–105 ] and MOFs [ 106,107 ] ). Especially, for metal chalcogenides, nitrides, and phosphides, they may be oxidized to the corresponding metal oxides/hydroxides in the oxidative environments of OER.…”
Section: Fundamentals Of Rechargeable Zn‐air Batteriesmentioning
confidence: 99%